Representasi Peran Ayah pada Film Avatar: The Way of Water - Muhammad Haikal MS; Firmansyah (Bandung Conference Series: Communication Management, 2024)
Abstract. The movie "Avatar: The Way of Water" presents an enchanting narrative about personal journeys and family dynamics amidst a magical fictional universe. The main focus is on the role of the father as the pillar of strength in a family faced with great challenges. Fathers serve not only as physical protectors of the family, but also as spiritual guides. In a world full of mystery and danger, the father becomes a source of inspiration for the main character, guiding him through obstacles and helping to shape his identity. Family decision-making becomes an important element in the narrative, where the father not only acts as the main decision-maker but also promotes collective decisions. This reflects the importance of collaboration and communication in the face of an unknown world. In the scenes of the father's role in this film will be analyzed starting from the denotation stage to the connotation stage. Researchers categorize the father roles that appear in this film into 8 forms of father roles, namely: (1) The role of a friend & playmate father in the form of a playmate, accompanying children to play and giving free time to talk with children. (2) The role of a caregiver father in the form of feeling comfortable, warm hugs and giving positive energy. (3) The role of father teacher & role model in the form of teaching children by providing education and input (4) The role of father monitor & disciplinary in the form of disciplining and sanctioning in the form of responsibility for actions taken. (5) The role of father protector in the form of protecting children outside and inside the home. (6) The role of a resource father is to support the family from behind the scenes. (7) The role of the decision maker father in the form of decision making and problem solving. (8) The role of the nurtured mother father in the form of a mother's companion or always protecting the mother's role in any condition. Abstrak. Film "Avatar: The Way of Water" menyajikan sebuah narasi yang mempesona tentang perjalanan pribadi dan dinamika dalam keluarga di tengah alam semesta fiksi yang ajaib. Fokus utamanya adalah pada peran ayah sebagai pilar kekuatan dalam keluarga yang berhadapan dengan tantangan besar. Ayah tidak hanya berfungsi sebagai pelindung fisik keluarga, tetapi juga sebagai pembimbing spiritual. Dalam dunia yang penuh misteri dan bahaya, ayah menjadi sumber inspirasi bagi karakter utama, membimbingnya melalui rintangan dan membantu membentuk identitasnya. Pengambilan keputusan keluarga menjadi elemen penting dalam narasi, di mana ayah tidak hanya berperan sebagai pengambil keputusan utama tetapi juga mempromosikan keputusan kolektif. Ini mencerminkan pentingnya kolaborasi dan komunikasi dalam menghadapi dunia yang belum dikenal. Dalam adegan peran ayah yang ada di dalam film ini akan dianalisis mulai dari tahap denotasi hingga ke tahap konotasi. Peneliti mengkategorikan peran ayah yang muncul dalam film ini menjadi 8 bentuk peran ayah, yaitu: (1) Peran ayah friend & playmate berupa teman bermain, menemani anak bermain dan memberi waktu luang untuk berbincang dengan anak. (2) Peran ayah caregiver berupa perasaan nyaman, pelukan hangat dan memberi energi positif. (3) Peran ayah teacher & role model berupa mengajari anaka dengan memberikan pendidikan dan masukan (4) Peran ayah monitor & disiplinary berupa mendisplinkan dan memberi sanksi dalam bentuk tanggung jawab atas perbuatan yang dilakukan. (5) Peran ayah protector berupa perlindungan anak di luar maupun di dalam rumah. (6) Peran ayah resource berupa mendukung keluarga dari belakang layar. (7) Peran ayah decision maker berupa pengambil keputusan dan memecahkan masalah. (8) Peran ayah nurtured mother berupa pendamping ibu atau selalu melindungi peran ibu dalam kondisi apapun.